The glycoconjugate-degrading enzymes of Clostridium perfringens: Tailored catalysts for breaching the intestinal mucus barrier. (30th May 2020) - Low, Kristin E; Smith, Steven P; Abbott, D Wade; Boraston, Alisdair B
Abstract: The gastrointestinal (GI) tract of humans and animals is lined with mucus that serves as a barrier between the gut microbiota and the epithelial layer of the intestine. As the proteins present in mucus are typically heavily glycosylated, such as the mucins, several enteric commensal and pathogenic bacterial species are well-adapted to this rich carbon source and their genomes are replete with carbohydrate-active enzymes targeted toward dismantling the glycans and proteins present in mucus. One such species is Clostridium perfringens, a Gram-positive opportunistic pathogen indigenous to the gut of humans and animals. The genome of C. perfringens encodes numerous carbohydrate-active enzymes that are predicted or known to target glycosidic linkages within or on the termini of mucus glycans. Through this enzymatic activity, the degradation of the mucosal layer by C. perfringens has been implicated in a number of GI diseases, the most severe of which is necrotic enteritis. In this review, we describe the wide array of extracellular glycoside hydrolases, and their accessory modules, that is possessed by C. perfringens, and examine the unique multimodularity of these proteins in the context of degrading the glycoconjugates in mucus as a potential component of disease.